TRADISI POTONG RAMBUT GORONTALO (HUNDINGO) - Abdul Rahmat (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
Islamic religion has given a very detailed attention on children,since the processes of conception, pregnancy, birth, to the education from a baby to adult. All stages get attention and careful guidance. It shows how important maintain, care for and educate children from the very beginning. In Islam, there are some manners or guidance in welcoming the birth of a baby in between hair clippers ceremony. Embodiments of the local language to a particular culture can be seen in various aspects ofthe culture. Hundingo, as one of the local cultures, uses Gorontalo language. It can be found on the application of the meaning of direct and indirect language or languages of verbal and nonverbal language. In hundingo ceremony, on the seventh day of the baby’s birth, it is suggested to cut the hair of the baby. This is as exemplified by Rasululah SAW when his grandsons Hasan and Husain werevborn. Prophet orderedto cut their hair and weigh the size of silver, then give in charity to the poor.